Influence of electroacupuncture on the points BP6 and E36 regarding gastric motility in Wistar rats - Carnevali, Taiane Rita; Da Silva E Silva, Fábio; Schuch, Luiz Filipe Dame; De Mattos Ferrasso, Marina [UNESP]; Carapeto, Luiz Paiva; De Oliveira Cavalcanti, Guilherme Albuquerque; Cleff, Marlete Brum (Universidade Estadual de Londrina, 2017)
The study aimed to evaluate by radiographic examination the action of electroacupuncture on gastric motility in experimental animals. We used 24 Wistar rats, three months old, that received five metallic spheres, via orogastric tube (OT), with 2mL of barium contrast, followed by treatments: electroacupuncture points E36 and BP6 (T1); electroacupuncture in stitches (T2); sterile distilled water OT (T3); metoclopramide OT (T4). After treatment, serial radiographs, hourly, were made to follow the gastric emptying time of the spheres in rats. By analyzing the time of exit of the first sphere, animals in the group T1 had an average of 3h30min; at T2 the average was higher 6 hours; in T3 was 5h18min, and T4 showed an average of 4h36min. The action of electroacupuncture was comparable to the action of metoclopramide, which is know to increase peristalsis, whereas the response of the Shan group (T2) was close to the negative control group. Considering the results it was concluded that electroacupuncture at points predetermined significantly increases gastric peristalsis, reducing gastric emptying time in rats, may be an option for the treatment of motility disorders.
Keywords: Acupuncture; Gastrointestinal; Radiography; Rats